Time-course mRNA sequencing on red drum (Sciaenops ocellatus) embryos exposed to slick oil (Gulf of Mexico Research Initiative, 2017)
This dataset contains total mRNA profiles of 24, 48, 72 hpf red drum larvae after slick oil exposure (0% or 2.5%). Data were generated by deep sequencing in triplicate, using Illumina HiSeq2500.